2022
DOI: 10.1515/cclm-2022-0345
|View full text |Cite
|
Sign up to set email alerts
|

Ad interim recommendations for diagnosing SARS-CoV-2 infection by the IFCC SARS-CoV-2 variants working group

Abstract: This document, endorsed by the IFCC Working Group on SARS-CoV-2 Variants, aims to update previous indications for diagnosing acute SARS-CoV-2 infection, taking into consideration the evidence that has emerged after the origin and spread of new lineages and sub-lineages of the virus characterized by mutated genetics and altered biochemical, biological and clinical characteristics. These indications encompass the use of different diagnostic strategies in specific clinical settings, such as high risk of SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Two recent economic analyses revealed that an approach based on sequential testing (SARS-CoV-2 Ag testing first, followed by NAAT in those testing negative) is not only clinically safe, but also is more costeffective than molecular testing alone [6,7]. As concerns the specific diagnostic performance of SARS-CoV-2 Ag testing, both the WHO [8] and the IFCC [5,9] mandate that minimum performance criteria shall be met by SARS-CoV-2 Ag immunoassays, either rapid diagnostic tests (RDT-Ag) or laboratory based, in that they should display ≥0.80 sensitivity and ≥0.97 specificity, respectively, when used in suspected COVID-19 cases (i.e., symptomatic subjects).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent economic analyses revealed that an approach based on sequential testing (SARS-CoV-2 Ag testing first, followed by NAAT in those testing negative) is not only clinically safe, but also is more costeffective than molecular testing alone [6,7]. As concerns the specific diagnostic performance of SARS-CoV-2 Ag testing, both the WHO [8] and the IFCC [5,9] mandate that minimum performance criteria shall be met by SARS-CoV-2 Ag immunoassays, either rapid diagnostic tests (RDT-Ag) or laboratory based, in that they should display ≥0.80 sensitivity and ≥0.97 specificity, respectively, when used in suspected COVID-19 cases (i.e., symptomatic subjects).…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO [4], a confirmed case of SARS-CoV-2 infection could be an individual with (i) a positive test result of a nucleic acid amplification test (NAAT) irrespective of other clinical or epidemiological criteria, or (ii) a positive test result of a professional used or self-test SARS-CoV-2 antigen (Ag) assay, meeting specific clinical (i.e., being symptomatic) or epidemiological (i.e., being a contact of a COVID-19 case or directly linked to a cluster) criteria. The International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) has recently endorsed similar recommendations, stating that the diagnosis of an acute SARS-CoV-2 infection can be made by either molecular or Ag testing, reserving the use of the second approach to specific clinical settings (i.e., especially in those at lower risk of an having acute SARS-CoV-2 infection or for specific epidemiological purposes) [5]. Two recent economic analyses revealed that an approach based on sequential testing (SARS-CoV-2 Ag testing first, followed by NAAT in those testing negative) is not only clinically safe, but also is more costeffective than molecular testing alone [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation